Factor structure and psychometric properties of the Anxiety Sensitivity Index in a sample of Croatian adults - Jurin, Tanja (Array, 2012)
Anxiety sensitivity (AS) refers to a person’s tendency to fear anxiety-related symptoms due to the belief that these symptoms may have harmful consequences. The most widely used operationalization of AS in adults is the Anxiety Sensitivity Index (ASI). The factor structure, gender stability, and psychometric properties of the ASI in a sample of Croatian adults (N = 984) were evaluated. Results confirm the multidimensional and hierarchical structure of the ASI, which consisted of three lower-order factors (Physical Concerns, Psychological Concerns, and Social Concerns) and a single higher-order factor, AS. Furthermore, the achievement of normative scores for the ASI in a Croatian adult sample demonstrates the cross-national stability of the ASI. Reliability coefficients for the ASI, Physical Concerns, and Psychological Concerns are high and satisfactory in the total sample and for both genders. Overall, the results confirmed the cross-national stability, gender stability, reliability, and validity of the ASI in a sample of Croatian adults.